Analysis of occurrence of bacteraemia with pathogens from gastrointestinal tract in patients fed parenterally and enterally in the intensive care unit - Jakubczyk, Marlena; Różowicz, Aleksandra; Spychalska, Katarzyna; Nakonowska, Beata; Kupczyk, Kinga; Kusza, Krzysztof (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Bacterial translocation is a migration of microorganisms and their toxins from the intestinal lumen to the mesenteric lymph nodes, blood, and abdominal organs. It can lead to local inflammatory response and a potential increase in intestinal permeability leading to systemic infections and multiple organ failure. Enteral nutrition stimulates gastrointestinal motility, increases blood flow, and improves the integration of the intestinal barrier. Aim : The impact of enteral (EN) and parenteral (PN) nutrition on occurrence of bacteraemia caused by pathogens from the gastrointestinal tract. Material and methods: It was a retrospective analysis of medical documentation of 254 patients. Microbiological tests were analysed, assessing the presence of bacteraemia or sepsis pathogens from the gastrointestinal tract. In 52 patients gastrointestinal pathogens in blood were found: 29 patients were fed enterally (I group – EN and EN + PN) and 23 only parenterally (II group – PN). Results : The mean length of stay in hospital until the occurrence of bacteraemia in group I was 14, and in group II it was 13 days. Mean time without EN was 4 days (first group) and 12 days (second group). Time of stay in ICU and mortality in the group of patients fed parenterally was observed: group I – 25 days, mortality 34%; group II – 37 days, mortality 56%. In the analysed group the EN and the length of the absence of this kind of feeding did not affect the occurrence of bacteraemia by gastrointestinal pathogens. Conclusions : However, patients fed only parenterally who had bacteraemia required a longer stay in the ICU and had a higher rate of mortality than the patients with EN.